2023
DOI: 10.3390/agronomy13030805
|View full text |Cite
|
Sign up to set email alerts
|

Three-Year Survey of Fusarium Multi-Metabolites/Mycotoxins Contamination in Wheat Samples in Potentially Epidemic FHB Conditions

Abstract: Fusarium head blight (FHB) is a fungal disease of cereals including wheat, which results in significant economic losses and reductions in grain quality. Additionally, the presence of Fusarium spp. results in productions of mycotoxins/metabolites, some of which are toxic in low concentrations. The liquid chromatography with tandem mass spectrometry (LC-MS/MS) method was applied to 216 wheat samples from field conditions diseased with FHB. Data obtained show that out of 28 metabolites detected, deoxynivalenol (D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 73 publications
0
4
0
Order By: Relevance
“…FHB and FCR are among the most significant wheat diseases worldwide [3]. They decrease yield, deteriorate wheat quality, and lead to grain contamination by mycotoxins-such as deoxynivalenol (DON) and its metabolites (3-AcDON, 15-AcDON), zearalenone (ZEA), nivalenol (NIV), fusarenone X (FusX), HT-2 toxin, T-2 toxin, and fumonisins (FUM)-which are one of the most toxic substances to humans and animals [4]. Despite the beneficial effects of biostimulators and pesticides in wheat protection, knowledge about their influence on plant metabolic status and physiological stress level, as well as their interactions with pathogenic fungi, remains insufficient.…”
Section: Introductionmentioning
confidence: 99%
“…FHB and FCR are among the most significant wheat diseases worldwide [3]. They decrease yield, deteriorate wheat quality, and lead to grain contamination by mycotoxins-such as deoxynivalenol (DON) and its metabolites (3-AcDON, 15-AcDON), zearalenone (ZEA), nivalenol (NIV), fusarenone X (FusX), HT-2 toxin, T-2 toxin, and fumonisins (FUM)-which are one of the most toxic substances to humans and animals [4]. Despite the beneficial effects of biostimulators and pesticides in wheat protection, knowledge about their influence on plant metabolic status and physiological stress level, as well as their interactions with pathogenic fungi, remains insufficient.…”
Section: Introductionmentioning
confidence: 99%
“…It is also one of the most widespread [2] and the most intensively studied wheat diseases [4]. Although significant progress has been made in the control of FHB, this disease remains a serious threat, especially in terms of accumulation of mycotoxins that are harmful to human and animal health [4][5][6]. The development and intensity of FHB can be conditioned by different factors related to host susceptibility and pathogen aggressiveness, but the most important are weather conditions during anthesis [5,7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Extreme weather conditions associated with climate change are expected to lead to various changes in Fusarium species, such as changes in seasonal phenology, population dynamics, and geographic distribution [9], while an increase in FHB epidemics as a result of global warming has already been recorded [10,11]. Effective FHB management requires a combination of cultural, biological, chemical, and host plant resistance strategies, where genetic control accomplished by breeding gains, when combined with other methods, may be a sustainable solution for FHB control [6,12]. However, breeding FHB resistant Plants 2023, 12, 3720 2 of 20 varieties with desirable agronomic traits is challenging because most sources of FHB resistance correlate with unfavorable agronomic traits [13].…”
Section: Introductionmentioning
confidence: 99%
“…However, many results indicated that the response of cultivars to the applied growing conditions varies and showed that individual wheat cultivars respond differently to the agro-technology used in cultivation, so it is important to select the production sys-tem individually according to the requirements, genetics, and production capacity of the cultivar [29][30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%